Metal Organic Framework — Based Mixed Matrix Membranes for Carbon Dioxide Separation: Recent Advances and Future Directions - Muthukumaraswamy Rangaraj, Vengatesan; Wahab, Mohammad A.; Reddy, K. Suresh Kumar; Kakosimos, George; Abdalla, Omnya; Favvas, Evangelos P.; Reinalda, Donald; Geuzebroek, Frank; Abdala, Ahmed; Karanikolos, Georgios N. (Frontiers in Chemistry, 2020)
Gas separation and purification using polymeric membranes is a promising technology that constitutes an energy-efficient and eco-friendly process for large scale integration. However, pristine polymeric membranes typically suffer from the trade-off between permeability and selectivity represented by the Robeson’s upper bound. Mixed matrix memebranes (MMMs) syntheisized by addition of porous nano-fillers into polymer matrices, can enable simultaneous increase in selectivity and permeability. Among the various porous fillers, MOFs are recognized in recent days as an effective filler material for the fabrication of MMMs. In this article, we review representative examples of MMMs prepared by dispersion of MOFs into polymer matrices or by deposition on the surface of polymeric membranes. Addition of MOFs into other continuous phases, such as ionic liquids, are also included. CO2 separation from hydrocarbons, H2, N2, and the like is emphasized. Hybrid fillers based on composites of MOF with other nanomaterials, e.g. of MOF/GO, MOF/CNTs, and functionalized MOFs, are also presented and discussed. Synergetic effects and the results of interactions between filler/matrix and filler/filler are reviewed and the effects of filler and matrix types and compositions, filler loading, surface area, porosity, pore sizes and surface functionalities on tuning permeability are discoursed. Finally, selectivity, thermal, chemical and mechanical stability of the resulting MMMs are analyzed. The review concludes with a perspective of up-scaling of such systems for CO2 separation, including an overview of the most promising MMM systems.